Auricularia (wood ear mushroom) genus: a contribution to classification and new species records for Iran and world - Akbar Jahedi; Naser Safaie; Ebrahim Mohammadi Goltapeh; Saeideh Ahmadifar (Plant and Fungal Systematics, 2024)
Auricularia is one of the most widely distributed macrofungi, regarded as an edible medical mushroom, and is the third largest cultivated mushroom in the world due to its high nutrition and bioactivity properties. This research specifies the taxonomic status of this genus in Iran for the first time. After sample collection during 2017–2018, 19 samples were collected from Hyrcanian forests in Iran. Phylogenetic analyses and morphological examinations of 19 samples were carried out. Morphological studies identified five species Auricularia auricula-judae , A. cornea , A. heimuer, A. iranica sp. nov., and A. mesenterica. Subsequently, one representative sample from each group (species) was sequenced. Based on rpb2 and ITS sequences, phylogenetic analyses were performed using Bayesian Inference analysis. The identification of five species of Auricularia was done according to molecular and morphological examinations. As expected from morphological characters, as well as ITS and rpb2 regions sequences support, one new species, Auricularia iranica in the A. mesenterica complex, is described. The two known species, A. auricula-judae and A. heimuer belonging to the A. auricula-judae complex and A. cornea belonging to the A. cornea complex, are defined. An identification key for the accepted Auricularia species of Iran is proposed.